Base de dados sobre conferências nacionais e um ensaio de análise lexical por contexto - Daniel Pitangueira de Avelino; Letícia Volpi Goulin (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Regarding one of the most renowned mechanisms of social participation in the recent Brazilian democracy, this paper aims to offer a typological proposal for national conferences, considering the broadened definition established by the Decree no 8243/2014 and ex post aspects of conferential processes. Thus, databases hosted by Ipea were updated and expanded, reaching the conferences held until 2016 and its approved resolutions from 2011 to 2016. This data collecting process put together a documental collection of 154 national conferences realized from 1941 to 2016, besides a database of 5,369 resolutions approved in 28 of the 42 conferences finished in the past five years. This table was submitted to a lexical analysis through the IRAMuTeQ software, according to the ALCESTE method. Briefly, five lexical worlds were observed, each holding its own characteristics. Also, the position of a specific conference in the class map can change between its editions, and this lexical displacement can occur under different ways. Some hypotheses - about lexical displacement and implicit territoriality - could be raised for further research, after this analysis. Thus, the availability of data, in a public and accessible way, may be a stimulus to the development of studies about this phenomenon or, at least, a factor for reduction of costs and efforts involved in this data collection.
Keywords: C88; D73; Z18; 330; national conferences; databases; lexical analysis; social participation